62 - INTEGRATIVE AND COMPLEMENTARY PRACTICES AT SUS: REFLECTION ABOUT PROFESSIONAL EDUCATION NEEDED TO PROVIDE THESE SERVICES TO POPULATION (Fiep Bulletin - online, 2011)
The concern in early prevention, promotion and restoration of health by means programs produced by Ministry of Health, allows measures implemented in services provided to monitor individuals health in general. However, in spite of having been institutionalized practices integrative and complementary (PICs) have not yet been firmly implemented in primary care institutions. The aim of this paper is to discuss the need for educational institutions to prepare health professionals as well as empower existing network in order to feel able to offer these practices to community, taking into consideration initiative of UFRN Nursing School of Natal (EEN-UFRN) to offer a course involving PICs. This initiative began when evaluating the need to provide Natal City to community and region, opportunities to develop those practices included in health units of Health Strategy of the Family. Therefore, acupuncture and yoga, two major areas of knowledge of Chinese Traditional Medicine and Ayurveda, are considered as basic structure of proposed technical school. Upon opening Federal Government to provide SUS user complementary health practices provided by network professionals duly empowered, TCM knowledge should be used as a way to implement and thus able to form health care workers facing such assistance. Added that the need to consider gestures and movements inherent in the human being as an expression of emotions and feelings. Thus may be offered to patients another alternative to remedy and/or minimize energy, organic dysfunctions, destabilizing their emotional well-being. In this situation, it is important to spread this initiative in other institutions forming health professionals. Thus health services make available to population PICs as a means of strengthening the health promotion through holistic approaches to stamp prevention.
Keywords: alternative therapies; training; health promotion